CONVERSION OF ENERGY BASED ON PHOTOVOLTAICS WITH INTEGRATED E-LEARNING - JINDROVA, Terezia (Trends in education, 2018)
We meet energy in all areas of physics, but also in other natural and technical subjects, or in ordinary life. It plays a central role in understanding the behavior of systems which are researching. We find it in various forms, and can be converted from one form to another (useful work). It is obviously one of the most important integral concepts of natural and technical sciences. One of the greatest challenges of didactics of these subjects is correctly understanding the concept energy. Innovative approaches are one of the forms which contribute to the effective teaching. They have motivational and activating character. Integrate e-learning is an example innovative approach to physics that connect real experiment with virtual experiment with the construction of physics knowledge. We focus on one of the areas of this concept and that is the transformation of energy - photovoltaics. Lights energy is converted to usable electricity energy by landing sun rays to the photovoltaic panel. We prepared a material for physics teachers where we analyzed the concept of energy conversion with the application of integrated e-learning. We contributed to the dissemination of innovation in physics teaching by active activity for students. It enable naturally construct new knowledge.
Keywords: Photovoltaic; transformation of energy; Integrate e-learning